Answer:
Exponential functions are patterns that get continuously multiplied by some number. It's exponential growth when the base of our exponential is bigger than 1, which means those numbers get bigger. It's exponential decay when the base of our exponential is in between 1 and 0 and those numbers get smaller.
24= 3*2^3
88= 11*2^3
664= 83*2^3 -> 83=11+72 = 11 + 2^3*3^2
664=2^3 (11+2^3*3^2) = 88 +(2^3*2^3*3^2) = 88 +(24^2)
8408= 1051 * 2^3 -> 1051= 83+968 -> 968 = 2^3 * 11^2
8408= 2^3 (83+2^3*11^2) = 664 +(2^3*2^3*11^2) = 664 +(88^2)
So:
a(n) = a(n-1) + a(n-2)^2
Lets check: 88+24^2= 664
664+88^2= 8408
The answer is -88
When you multiply and then divide
Okay so we get: subtract m + 8 from 5m + 11
5m + 11 = 16 + m or 16m
16m - 8 +m or 8m = 8m or 8 + m